Strike Activities and Post-Strike Perceptions Among University Faculty - Ng, Ignace (Relations industrielles / Industrial Relations, 1993)
Based upon the returned questionnaires of 415 striking faculty members from the University of Saskatchewan, this study shows that faculty members who have attended the study session, and those who have been active in past union meetings were more likely to get involved in picketing and in picket organizing during the course of the strike. Analysis of their post-strike perceptions shows that the faculty attitudes towards the effectiveness of the strike, strike length, and back-to-work legislation were closely related to the militancy of the faculty during the strike.